Pengaruh Perbandingan Tepung Kacang Merah (Phaseolus vulgaris. L) dan Tepung Daun Pegagan(Centella asiatica (L.) Urban) Terhadap Karakteristik Cookies - Siahaan, Bobby Frans; Yusa, Ni Made; Pratiwi, I Desak Putu Kartika (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 3 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i03.p20, 2021)
This research was aimed for determine the effect of comparison red bean flour and Centella leaf flour on the characteristics of cookies produced and the comparison red bean flour and Centella leaf that is able to produced cookies with the best characteristics. The research based on a Completely randomized design (CRD) with treatment the ratio of red bean flour and Centella leaf flour consisting of 5 levels: 97%: 3%; 94%: 6%; 91%: 9%; 88%: 12%; 85%: 15%. Each treatment was replicated 3 times to obtain 15 experimental units. Data was analyzed using analysis of variance and if the treatment had a significant effect, its followed by the Duncan multiple range test (DMRT). The results showed that the comparison of red bean flour and Centella leaf flour has a significant effect to crude fiber content, protein content, and antioxidant capacity, colour, texture, taste and overall acceptance (hedonic), colour, texture and taste (skoring). Ratio of 91% red bean flour and 9% Centella leaf flour for producing cookies the best characteristics with a moisture content 4.28%, crude fiber content 19.87%, protein content 9.33% and antioxidant capacity 85.60%, color is greenish brown and liked, texture is crunchy and liked, taste is somewhat distinctive of Centella leaf and very liked, aroma and overall acceptance were liked.